The Analysis of Dilation Morphology for Quality Improvement of the Edge Detection Imagery on Batik Patterns using Prewitt Operator and Laplacian of Gaussian - Muhammad Abrar Masril; Refli Noviardi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
The results of the edge detection process using several operators are not yet optimal. Therefore we need a method to improve the quality of edge detection images, the method used in this study is morphology dilation. The results of testing the improvement of image quality using 10 batik patterns, resulting in an accuracy level on Laplacian of Gaussian operators is 80% and for Prewitt operators is 60%. In the process of improving the edge detection quality, Morphology Dilation can connect broken edges using structuring elements. therefore it can improve the quality of edge images.